2017
DOI: 10.3389/fpls.2017.01324
|View full text |Cite
|
Sign up to set email alerts
|

Laccase-13 Regulates Seed Setting Rate by Affecting Hydrogen Peroxide Dynamics and Mitochondrial Integrity in Rice

Abstract: Seed setting rate is one of the most important components of rice grain yield. To date, only several genes regulating setting rate have been identified in plant. In this study, we showed that laccase-13 (OsLAC13), a member of laccase family genes which are known for their roles in modulating phenylpropanoid pathway and secondary lignification in cell wall, exerts a regulatory function in rice seed setting rate. OsLAC13 expressed in anthers and promotes hydrogen peroxide production both in vitro and in the fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 67 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…Our results matched the concomitant increase in ferroxidase activity and ROS generation in mutant 408-KO under Fe scarcity conditions compared to the WT (Figures 6B, 7A). The results shown herein also agree with the proposed role of LMCOs functioning as ascorbate oxidases and, subsequently, with increasing H 2 O 2 levels by competing with ascorbate peroxidases for reduced ascorbate (Yu et al., 2017). Hence according to the levels of the miR408 target LMCOs (Figures 3, 7A), H 2 O 2 levels increased in mutant 408-KO and decreased in the 35S:408-14 line compared to the WT.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results matched the concomitant increase in ferroxidase activity and ROS generation in mutant 408-KO under Fe scarcity conditions compared to the WT (Figures 6B, 7A). The results shown herein also agree with the proposed role of LMCOs functioning as ascorbate oxidases and, subsequently, with increasing H 2 O 2 levels by competing with ascorbate peroxidases for reduced ascorbate (Yu et al., 2017). Hence according to the levels of the miR408 target LMCOs (Figures 3, 7A), H 2 O 2 levels increased in mutant 408-KO and decreased in the 35S:408-14 line compared to the WT.…”
Section: Discussionsupporting
confidence: 87%
“…H 2 O 2 scavenging in the culture medium significantly decreases the amount of extracellular lignin formed in Norway spruce, and the inhibition of superoxide (normalO2) synthesis, or its dismutation to H 2 O 2 by superoxide dismutases reduces lignin content (Kärkönen et al., 2002; Karlsson et al., 2005). Rice OsLAC3 has been shown to induce H 2 O 2 accumulation, which affects the seed setting rate and mitochondria integrity in vascular tissues and root tips (Yu et al., 2017). Given the striking similarity between OsLAC3 and L-ascorbate oxidases, a role in oxidizing ascorbate, which drives to restrain H 2 O 2 removal, has been proposed to explain the observed phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Laccases (LACs) belong to a large group of enzymes termed blue copper proteins, which include ascorbic acid oxidase and plastocyanin. A previous study has shown that OsLAC13 can produce H 2 O 2 and is regulated by miRNA397 [69]. In this study, seven miRNA397a/b target genes were identified as being from the LAC family, including 2 laccase-13, 2 laccase-3, 2 laccase-10 and 1 laccase-4.…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, AtLAC15 was involved in two different phenotypes, seed coat coloration and root elongation, both linked to lignin (Liang et al, 2006). OsLAC13 regulated the seed setting rate in rice by suppressing the transport of sugars to the anthers and promoting H 2 O 2 production through unknown mechanisms (Yu et al, 2017). However, heterologous expression of OsLAC10 in Arabidopsis plants increased lignification around vasculature and increased Cu stress tolerance (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%